Simulation Study on the Development Process and Phase Interface Structure of Gas-Liquid Slug Flow in a Horizontal Pipe - Wu, Xiao; Wang, Zhaoting; Dong, Mei; Ge, Quan; Dong, Longfei (Frontiers in Energy Research, 2021)
Here, a unified 3D numerical model of gas-liquid two-phase flow in a horizontal pipe was established using the interface capture method based on the open source software package OpenFOAM. Through numerical simulation of the natural slugging and development process of slug flow under different working conditions, the motion, phase interface structure, pressure and velocity field distributions of the liquid slug were fully developed and analyzed. The simulation results are consistent with the experiment. The results showed that during the movement of the slug head, there is a throwing phenomenon and a wave-like motion of the liquid slug. In addition, the slug tail and body area have very similar velocity profiles, and the overall velocity field distribution becomes more uniform with the development of liquid slug. Moreover, there are sudden pressure fluctuations at the head and tail of the liquid slug.